(3GdCWYeIs - (3CHh Ydj CMeO Hf YHO GdQMef, GHf efOhjg GdCUagGfj,J (B372 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hUdhGJg Ydi NjQ GdNdGFb eMeO hBdg CLeYjf GdWGgQjf bGd (B: (3CMeO Hf efOhjI (B: (3Cf ehbY GdCbhGJ ef GdCLSGO ahb ehbY cd eMJGL Gdjg ai eUdMJgG s
(3BNQgG (B:s
(3MJi EPG LdS hhVY Ydi GdWHb , UGQ Yfbg ai Pdc GdJbhjQ hQCSg NGQLkG efg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B171 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK HESJGfHhd (B(2040(2)) s
Keywords: (3GdUfGYI hGdCWYeIs